Genocidal Dimensions of the Russo-Ukrainian War: Targeting the People and Cultural Heritage of Ukraine - Baženova, Hana (Genocidas ir rezistencija, 2024)
When the Russian Federation launched a full-scale aggression against Ukraine, it violated the prohibition on the “use of force against the territorial integrity or political independence of any state”, embodied in Article 2, paragraph 4, of the United Nations Charter. The crimes committed by the Russian armed forces since 24 February 2022 in Ukraine constitute the most serious crimes of international concern, as confirmed by the International Criminal Court’s arrest warrant for Russian President Vladimir Putin and the Presidential Commissioner for Children’s Rights Maria Alekseyevna Lvova-Belova in connection with specific acts classified by this court as war crimes. At the same time, to constitute a crime of genocide, there must be a proven intent on the part of the accused to destroy, in whole or in part, a national, ethnical, racial, or religious group. This article examines the war crimes perpetrated by the Russian armed forces against the civilian population of Ukraine during the Russo-Ukrainian war and identifies signs of genocidal intent in these actions. It analyses explicit acts of genocide including killings, causing serious bodily or mental harm, the forced transfer of Ukrainian children to Russia and occupied territories, and the intentional creation of living conditions geared toward the physical destruction of the Ukrainians as a nation. Additionally, the article scrutinises the attacks on the country’s cultural heritage sites, which in turn can be qualified depending on the circumstances, as war crimes (when, inter alia, military necessity is not justified and the principle of distinguishing between military and civilian targets is violated), crimes against humanity (when they are systematic), or genocide (when they are part of a policy of identity destruction). The author demonstrates that Russian aggression against Ukraine not only poses a threat to the territorial integrity and state sovereignty of the country, but also seeks to annihilate – at least partially – the Ukrainian nation, its identity, and its cultural heritage. The Russo-Ukrainian conflict exhibits signs of a genocidal campaign that are recognised by international law under the 1948 Genocide Convention. This is manifested in an attempt to commit genocide, direct and public incitement for genocide, and the commission of genocide in certain territories, specifically in Bucha and Mariupol. However, substantiating and proving the crime across all of Ukraine will be more difficult and may take years. An exception to this challenge is the mass transfer of almost 4,500 Ukrainian orphans to Russia – a crime that concerns the entire country. Additionally, acts of torture and killings that occurred in the early stages of the full-scale invasion (February and March 2022) in the Kyiv and Chernihiv regions exhibit signs of genocide committed in certain territories. At the same time, the existing facts, viewed through a historical prism, indicate that the actions taken by Russian forces in Ukraine embody the characteristics of genocide.